Emerging Parvoviruses in Domestic Cats - Paolo Capozza; Vito Martella; Canio Buonavoglia; Nicola Decaro (Viruses, 2021)
Parvovirus infections in cats have been well known for around 100 years. Recently, the use of molecular assays and metagenomic approaches for virus discovery and characterization has led to the detection of novel parvovirus lineages and/or species infecting the feline host. However, the involvement of emerging parvoviruses in the onset of gastroenteritis or other feline diseases is still uncertain.